Cloning and characterization of the hemolysin determinants from Vibrio cholerae RV79(Hly+), RV79(Hly-), and 569B. - Goldberg, S L (1985)
The Hly region from the chromosome of Vibrio cholerae El Tor strain RV79(Hly-) and the nonhemolytic classical strain 569B were cloned into plasmid vector pBR322. Escherichia coli K-12 transformants possessing these recombinant plasmids were nonhemolytic and were detected with a 32P-labeled hly-specific DNA probe. Restriction endonuclease Sau3AI digestions of the cloned hly loci of two independently obtained RV79(Hly+) convertants, when compared with the digests of cloned RV79(Hly-) loci, revealed that an apparent alteration (10 to 15 base pairs) had occurred. In contrast, an apparent 20-base-pair deletion was present in the cloned hly locus of the classical biotype V. cholerae strain 569B. Maxicell analysis and immunoprecipitation of labeled proteins of E. coli which are encoded by the cloned hly loci of RV79(Hly+) and from nuclease BAL 31-deleted plasmids, as well as immunoprecipitation of [35S]methionine-labeled V. cholerae proteins, suggest that the hemolysin is an 84,000-dalton polypeptide.